A Weak form of Hadwiger's Conjecture - Dominic van der Zypen, (Journal of Basic & Applied Sciences, 2014)
We introduce the following weak version of Hadwiger's conjecture: If G is a graph and is a cardinal such that there is no coloring map c:G, then K is a minor of G. We prove that this statement is true for graphs with infinite chromatic number.